Pengaruh Fashion Consciousne, Materialism dan Fashion Involvement terhadap Keputusan Pembelian Batik oleh Anak Muda di Indonesia - Lestari, Marlina Dewi; Santoso, Adi; Riawan, Riawan (Ekonomis: Journal of Economics and Business, 2024)
The aim of this research is to determine the influence of fashion consciousness, materialism and fashion involvement on batik purchasing decisions by young people in Indonesia. The population of this research is young people who purchase batik products in Indonesia. The sample size for this research was 352 respondents. Where this amount is obtained using the ISAC table. This type of research data is primary data obtained through distributing questionnaires online using Google Form. The data analysis method for this research uses the SEM method with the Smart PLS statistical tool. The results of this research are that fashion consciousness, materials, fashion clothing involvement influence purchases.